Combining Pre- and Postoperative Lymphocyte–C-Reactive Protein Ratios Can Better Predict Hepatocellular Carcinoma Prognosis After Partial Hepatectomy - Ni HH; Lu Z; Huang X; Ning SW; Liang XL; Zhang SY; Xiang BD (Dove Medical Press, 2022)
Hanghang Ni,1,2,* Zhan Lu,1,2,* Xi Huang,1 Shangwu Ning,1 Xiaoling Liang,1 Shuyi Zhang,1 Bangde Xiang1- 3 1Department of Hepatobiliary Surgery, Guangxi Medical University Cancer Hospital, Nanning, People's Republic of China; 2Key Laboratory of Early Prevention and Treatment for Regional High-Frequency Tumors, Ministry of Education, Nanning, People's Republic of China; 3Guangxi Liver Cancer Diagnosis and Treatment Engineering and Technology Research Center, Nanning, People's Republic of China*These authors contributed equally to this workCorrespondence: Bangde Xiang, Department of Hepatobiliary Surgery, Guangxi Medical University Cancer Hospital, 71 Hedi Road, Qingxiu District, Nanning, Guangxi, 530021, People's Republic of China, Tel +86-7715301253, Email xiangbangde@gxmu.edu.cnBackground: Various preoperative inflammatory indicators have been identified as potential predictors of poor prognosis in patients with hepatocellular carcinoma (HCC), but the role of postoperative inflammatory indicators remains unclear. This study aimed to explore the prognostic value of the postoperative lymphocyte-C-reactive protein ratio (PostLCR) on its own and combined with preoperative LCR (PreLCR).Methods: A total of 290 patients with primary HCC were retrospectively enrolled in the study. Univariate analysis was used to identify factors significantly associated with poor disease-free survival (DFS) and overall survival (OS), then multivariate analysis was performed to identify independent prognostic indicators of poor survival. Prognostic models based on preoperative, postoperative, and both types of indicators were then constructed, and their predictive performance were evaluated using time-dependent receiver operating characteristic curves and the concordance index (C-index).Results: PreLCR and PostLCR levels correlated with DFS and OS more strongly than other pre- and postoperative inflammatory indicators, respectively. Decreased PreLCR and PostLCR were independent prognostic factors for both DFS and OS, while HCC patients with decreased PreLCR and PostLCR had worse prognosis than patients with increased PreLCR and PostLCR. Patients into three groups based on their cut-off values of PreLCR and PostLCR, Kaplan-Meier survival analysis indicated that HCC patients with low PreLCR and PostLCR had the worst DFS and OS. The combined model showed better predictive performance at 1 and 3 years post-surgery than individual pre- and postoperative models, the American Joint Committee on Cancer/Tumor-Node-Metastasis (8th edition) staging system and the Barcelona Clinic Liver Cancer system. The combine model demonstrated a markedly superior C-index compared with the other models in DFS and OS.Conclusion: Our study showed PreLCR and PostLCR are independent predictors of DFS and OS in HCC patients after partial hepatectomy. Models that include both PreLCR and PostLCR can predict prognosis better than well-established clinical staging systems.Keywords: hepatocellular carcinoma, lymphocyte-to-C-reactive protein ratio, partial hepatectomy, disease-free survival, postoperative